Linkage mapping of the gpdA gene of Aspergillus nidulans - P. J. PUNT; P. A. GREAVES; CAM J. J. VAN DEN HONDEL (Fungal Genetics Reports, 1990)
In the last few years many genes of several Aspergillus species have been cloned and sequenced. For many of these genes mutant alleles and genetic linkage data are also available. However, for those genes for which no mutant alleles have been isolated, genetic mapping was not possible. Here we report linkage mapping of the glyceraldehyde-3- phosphate dehydrogenase gene (gpdA) of A. nidulans for which no mutant alleles have been isolated. The method used is applicable to all other cloned genes.